Comparison of Inverter Types for Home Appliance Using Push-Pull Amplifier - Mokh Hairul Bahri; Dudi Irawan (Logic : Jurnal Rancang Bangun dan Teknologi, 2021)
This paper deals with a comparison of inverter types and develops a system to provide pure sine wave ac voltage. The ac voltage is utilized to drive the compressor ac split. The assembled inverter problem is a square waveform, power losses, torque, efficiency, and a lag behind in terms of performance reliability. The push-pull amplifiers technic is proposed to produce sine wave output from dc input. The output result shows that an experimental pure sin wave obtains a frequency of 50.05 Hz, V max 13.49 Volt, V min -14.49 volt, and duty cycle 50.1%. the assembled inverter has a frequency is 37.87 Hz, V max 11.88 Volt, V min 13.09 volt, and a duty cycle is 50 %. A modified 3-phase inverter attains frequency 50.05 Hz, V max 15.71 Volt, V min -16.11 Volt, and the duty cycle is 50.5 %. The frequency, v max, v min, and duty cycle are bigger than an assembled inverter, then the modified 3-phase inverter has small harmonic distortion. The comparison of inverter types gives information for home appliances.